Analysis of anti-rheumatic activity of Nyctanthes arbor-tristis via in vivo and pharmacovigilance approaches - Ayushi Sharma; Anjana Goel; Zhijian Lin (Frontiers Media S.A., 2023)
Introduction: Rheumatoid arthritis (RA) is an immune-mediated disease associated with chronic inflammation of numerous joints. Nyctanthes arbor-tristis (NAT) is a traditional remedy for RA, a chronic inflammatory disorder.Aim: The current project aims to demonstrate the role of the NAT extracts in sub-acute toxicity, pharmacovigilance, and anti-rheumatic biomarkers.Method: Hydroethanolic extract (1:1) of plant leaves was prepared by using the reflux method. The safety of the dose was evaluated in Sprague-Dawley rats, and the anti-inflammatory effects of NAT on RA symptoms, including paw volumes, body weight, arthritic index, withdrawal latency, hematology and serological test, radiology, and histopathology, were evaluated in Freund's complete adjuvant (FCA)-induced arthritis Sprague-Dawley rat models. The inflammatory (TNF-α and COX-2) and anti-inflammatory markers (IL-10) were analyzed in control and experimental groups.Result: The study showed that 500 mg/kg BW NAT leaf extract was found to be least toxic without showing any subacute toxicity symptoms. The pharmacovigilance study highlighted the potential side effects of NAT, such as drowsiness, sedation, and lethargy, at high dosages. Treatment with the plant extract mitigated paw edema, restored the immune organ and body weights, and ameliorated the level of blood parameters such as hemoglobin, red blood cells, platelets, white blood cells, aspartate aminotransferase (AST), alanine transaminase (ALT), C-reactive proteins, and rheumatoid factor. Treatment with the plant extracts also reduced the level of cyclooxygenase 2 and TNF-α and increased the level of IL-10 in the serum of arthritic rats dose-dependently. Radiographic analysis of the ankle joint showed an improvement in the hind legs. Histological examination of the ankle joints revealed that the plant extract treatment decreased pannus formation, inflammation, and synovial hyperplasia in arthritic animals.Conclusion: NAT 500 mg/kg could serve as a promising therapeutic option for the treatment of inflammatory arthritis.